Behavioral Economics Comes of Age: A Review Essay on Advances in Behavioral Economics - Pesendorfer, Wolfgang (Journal of Economic Literature, 2006)
Advances in Behavioral Economics contains influential second-generation contributions to behavioral economics. Building on the seminal work by Kahnemann, Strotz, Thaler, Tversky, and others, these contributions have established behavioral economics as an important field of study in economics. In this essay, I discuss aspects of the research strategy and methodology of behavioral economics, as exemplified by the contributions to Advances.